[tex]\dfrac{\sqrt[3]{3x^2-1}+\sqrt{2x^2+1}}{1-\cos x}=\dfrac{\sqrt[3]{3x^2-1}+\sqrt{2x^2+1}}{2\sin ^2\dfrac{x}{2}}=\dfrac{\sqrt[3]{3x^2-1}+\sqrt{2x^2+1}}{2.\dfrac{x^2}{4}}.\left ( \dfrac{\dfrac{x}{2}}{\sin \dfrac{x}{2}} \right )^2[/tex]
[tex]=2.\dfrac{\sqrt[3]{3x^2-1}+\sqrt{2x^2+1}}{x^2}.\left ( \dfrac{\dfrac{x}{2}}{\sin \dfrac{x}{2}} \right )^2[/tex]
Ta sẽ tìm [tex]\lim _{x\to 0}\dfrac{\sqrt[3]{3x^2-1}+\sqrt{2x^2+1}}{x^2}[/tex]
[tex]=\lim _{x\to 0}\dfrac{\sqrt[3]{3x^2-1}+1+\sqrt{2x^2+1}-1}{x^2}[/tex]
[tex]=\lim _{x\to 0}\dfrac{\dfrac{3x^2}{\sqrt[3]{(3x^2-1)^2}-\sqrt[3]{3x^2-1}+1}+\dfrac{2x^2}{\sqrt{2x^2+1}+1}}{x^2}[/tex]
[tex]=\lim _{x\to 0} \left [\dfrac{3}{\sqrt[3]{(3x^2-1)^2}-\sqrt[3]{3x^2-1}+1}+\dfrac{2}{\sqrt{2x^2+1}+1} \right ][/tex]
[tex]=\dfrac{3}{3}+\dfrac{2}{2}=2[/tex]
Lại có [tex]\lim _{x \to 0}\dfrac{\dfrac{x}{2}}{\sin \dfrac{x}{2}}=1[/tex] nên [TEX]\lim _{x \to 0} \dfrac{\sqrt[3]{3x^2-1}+\sqrt{2x^2+1}}{1-\cos x}=4[/TEX]